Analisis Keseimbangan Lini Produksi untuk Mengurangi Work In Process (WIP) pada UD. Dandang Cap Banteng - Mohammad Ravanda Habiburrahman; Sajiyo Sajiyo (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
UD. Dandang Cap Banteng is an aluminum household appliance manufacturing industry that experiences problems in the form of Work In Process (WIP) accumulation and workload imbalance between work stations. This study aims to determine the level of production efficiency and design a production line balance using the Ranked Positional Weight (RPW) method. The study was conducted on the production process of 32-sized rice steamers using the stopwatch time study and Line balancing methods. The results showed that the total standard production time was 1539 seconds and there was a bottleneck in the assembly process. After implementing the RPW method, 5 work stations were obtained with a Line efficiency of 89% and a balance delay of 11%, thus reducing the accumulation of WIP and smoothing the production flow. This study shows that the implementation of Line balancing using the RPW method can improve the efficiency of the production line in the company.